Adaptation can help mitigation: An integrated approach to post-2012 climate policy - Francesco Bosello; Carlo Carraro; Enrica De Cian (Fondazione Eni Enrico Mattei (FEEM), 2011)
The latest round of international negotiations in Copenhagen led to a set of commitments on emission reductions which are unlikely to stabilise global warming below or around 2êC. As a consequence, in the absence of additional ambitious policy measures, adaptation will be needed to address climate-related damages. What is the role of adaptation in this setting? How is it optimally allocated across regions and time? To address these questions, this paper analyses the optimal mix of adaptation and mitigation expenditures in a cost-effective setting in which countries cooperate to achieve a long-term stabilisation target (550 CO2-eq). It uses an Integrated Assessment Model (AD-WITCH) that describes the relationships between different adaptation modes (reactive and anticipatory), mitigation, and capacity-building to analyse the optimal portfolio of adaptation measures. Results show the optimal intertemporal distribution of climate policy measures is characterised by early investments in mitigation followed by large adaptation expenditures a few decades later. Hence, the possibility to adapt does not justify postponing mitigation, although it reduces its costs. Mitigation and adaptation are thus shown to be complements rather than substitutes.
Keywords: Q54; Q56; Q43; 330; Climate Change Impacts; Mitigation; Adaptation; Integrated Assessment Model